Optimization of the Heterologous Expression of the Cannabinoid Type-1 (CB1) Receptor - Horváth, Viktória B.; Soltész-Katona, Eszter; Wisniewski, Éva; Rajki, Anikó; Halász, Eszter; Enyedi, Balázs; Hunyady, László; Tóth, András Dávid; Szanda, Gergő (Frontiers in Endocrinology, 2021)
The G protein-coupled type 1 cannabinoid receptor (CB1R) mediates virtually all classic cannabinoid effects, and both its agonists and antagonists hold major therapeutic potential. Heterologous expression of receptors is vital for pharmacological research, however, overexpression of these proteins may fundamentally alter their localization pattern, change the signalling partner preference and may also spark artificial clustering. Additionally, recombinant CB1Rs are prone to intense proteasomal degradation, which may necessitate substantial modifications, such as N-terminal truncation or signal sequence insertion, for acceptable cell surface expression. We report here that tuning down the expression intensity of the full-length CB1R reduces proteasomal degradation and offers receptor levels that are comparable to those of endogenous CB1 receptors. As opposed to high-efficiency expression with conventional promoters, weak promoter-driven CB1R expression provides ERK 1/2 and p38 MAPK signalling that closely resemble the activity of endogenous CB1Rs. Moreover, weakly expressed CB1R variants exhibit plasma membrane localization, preserve canonical Gi-signalling but prevent CB1R-Gs coupling observed with high-expression variants. Based on these findings, we propose that lowering the expression level of G protein-coupled receptors should always be considered in heterologous expression systems in order to reduce the pressure on the proteasomal machinery and to avoid potential signalling artefacts.